426 Bi-directional association between stress and musculoskeletal pain: 1-year prospective cohort study with weekly registrations. (24th April 2018) - Pihl-Thingvad, J; Andersen, JH; Andersen, LL; Brandt, LPA
Abstract : Introduction: Stress and musculoskeletal pain are major reasons for sickness absence. Although stress and pain are considered two different disorders and therefore treated and prevented separately, recent years research suggest that they may influence and reinforce each other. The objective of the present study was to investigate the prospective association between perceived stress and musculoskeletal pain. Methods: A cohort of 6943 technical assistants and machine technicians across Denmark participated in the NUDATA (Neck and Upper extremity Disorders Among Technical Assistants) study. Participants replied to a baseline and 12 month follow-up questionnaire about work and health. In between baseline and follow-up, they replied to weekly questions about perceived stress and musculoskeletal pain. The year was separated in three equal phases. Prospective associations between stress and pain were modelled using generalised estimating equations. The predictor variable was in phase 2 and the outcome variable in phase 3, always adjusted for phase 1. The models were further controlled for gender, age, physical and psychosocial work environment, lifestyle, education, chronic disease, mental health, multisite pain, musculoskeletal accidents, and baseline value of the outcome. Result: Perceived stress significantly increased the odds for pain in the neck (OR 2.10), shoulders (OR 2.02), elbow (OR 2.63), forearm (OR 1.93) and hand (OR 3.56). For the opposite association, shoulder pain (OR 2.37), forearm pain (OR 1.85) and hand pain (OR 1.90) significantly increased the odds of stress. Discussion: Our prospective study showed that while stress increases risk of pain in the neck and upper extremities, such pains also increases the risk of stress. The study supports existing findings from both experimental and brain research, proposing that development of stress and pain should be seen as separate but intertwined processes. Further research should be conducted to better understand the mechanisms of this interaction.